About reality: Relations between museums and virtual reality1. Issue 1 (1st December 2019) - Gobira, Pablo; de Oliveira Silva, Emanuelle
AbstractIn this article we discuss how museums, as knowledge institutions, enable the public to use virtual reality (VR) as an instrument for exhibitions. Most current research is about integrating VR into the traditional frame of a museum to enable a deeper and more meaningful understanding of the displayed artworks. This happens because of a narrow view of the concept of 'reality'. To start this discussion we are going to broaden the concept of 'reality', and go beyond the most commonly used terms of real and virtual. We will study some case applications of VR in museums and the way it is understood, to then bring about the range of possibilities it has beyond the common use. We will work with the most widely accepted theories on museums and based on Roy Ascott's works we will present a deeper discussion on the topic of realities.